Oral Surgery Procedures in a Patient Affected by Hereditary Angioedema Type I - Chiara Cinquini; Simonetta Santarelli; Alberto Marianelli; Marco Nisi; Mario Gabriele; Antonio Barone (Case Reports in Dentistry)
Hereditary Angioedema (HAE) is a rare disease characterized by a deficiency or a reduced function of the plasma protein C1 esterase inhibitor (C1-INH), which is involved in the downregulation of several inflammatory pathways. Patients affected by HAE suffer from episodic swellings of subcutaneous or submucosal tissues. Swellings can be caused by stress or dental and surgical procedures and can be life-threatening if the airways are involved. We have reported a clinical case of a patient affected by HAE type I who underwent oral surgery procedures under a short-term prophylaxis with C1-INH plasma-derived concentrate. The patient underwent a cyst removal, multiple tooth extractions, and an excisional biopsy with a prophylaxis with C1-INH plasma-derived concentrate and was hospitalized for 36 hours after the surgery to be monitored for possible HAE attacks. During the hospitalization, the patient did not show signs of swelling nor of HAE attacks. At 14 and 28 days after the surgery, the patient presented a good surgical healing. The prophylactic intravenous infusion of C1-INH concentrate was successful in preventing acute HAE attacks after oral surgery procedures.